How Does Governance Quality Affect Education: A Theoretical Framework - Mert TOPCU (Research Retrieval and Academic Letters, 2023)
Education quality is influenced by factors several factors including the social, economic, and cultural dynamics. Among these dynamics, one of the crucial factors is governance quality, which can affect educational outcomes through several channels. This study provides a theoretical discussion on how governance quality affects education and offers four broader transmission mechanisms: (i) resource allocation and efficiency, (ii) institutional quality and accountability, (iii) social inclusivity and access, and (iv) stability and long-term planning.